Pengaruh Media Pembelajaran Terhadap Prestasi Siswa di SD Islam Darul Falah Kemlokologi Baron - Mufidah, Luluk Indarinul (MASALIQ, 2025)
This study is motivated by the lack of in-depth research related to the use of learning media in the context of Islamic elementary schools, particularly at SD Islam Darul Falah Kemlokolegi Baron. The effectiveness of learning media is believed to have a significant impact on students' learning outcomes. The main objective of this research is to analyze the extent to which learning media contributes to students' academic achievement. The research approach used is qualitative, with data collection through observations, interviews with teachers and students, and available documentation. The findings of this study support constructivist theory, which states that learning becomes more meaningful when students are actively involved through suitable media. The main conclusion of this research indicates that the appropriate use of learning media can enhance students' motivation and understanding, which ultimately positively impacts the improvement of learning achievement. Theoretically, the results of this study enrich the discussion on the effectiveness of media in the learning process at the elementary school level. Practically, these findings provide recommendations for teachers and school authorities to be more selective and innovative in choosing and developing contextual and engaging learning media. This research also opens opportunities for further exploration of other variables that may also affect students' achievement, such as learning styles, parental involvement, or the learning environment at home.